PENGARUH EARNINGS PER SHARE, ECONOMIC VALUE ADDED, MARKET SHARE, DAN NET CASH FLOW TERHADAP RETURN SAHAM (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR KERAMIK PORSELIN DAN KACA YANG TERDAFTAR DI BEI 2011-2015) - Erlita Tyas Puspa Marhaeni (INVENTORY: JURNAL AKUNTANSI, 2017)
The purpose of this research is to determine whether there is the influence of earning per share, economic value added, market share, and net cash flow to return of both simultaneously and partial. The population in this study is a company manufacturing the ceramic, porcelain and glass are listed on the BEI in 2011-2015. The study used data from secondary in the form of financial statements the company.Testing this hypothesis using regression linear and through augmented with partial test, simultan test, and coefficient of determination. The result in partial to show that a market share and net cash flow, have a significant effect on return, while earning per share and economic value added don’t have a significant effect on return. In a simultaneous variable earning per share, economic value added , market share and net cash flow together have a significant effect on return. Manufacturing companies the industrial ceramics, porcelain and glass need to increase the company’s performance in achieving market share and net cash flow are higher because it will provide a significant impact on the return. Keyword: Earning Per Share, Economic Value Added, Market Share, Net Cash Flow, Return